2019
DOI: 10.1186/s13014-019-1242-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between radiation doses to coronary arteries and location of coronary stenosis requiring intervention in breast cancer survivors

Abstract: Background To assess the relationship between radiation doses to the coronary arteries (CAs) and location of a coronary stenosis that required intervention after three-dimensional conformal radiotherapy (3DCRT) for breast cancer (BC). Methods The study population consisted of 182 women treated for BC in Sweden between 1992 and 2012. All women received 3DCRT and subsequently underwent coronary angiography due to a suspected coronary event. CA segments were delineated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 24 publications
1
61
0
Order By: Relevance
“…In a recent systematic review of trials from 2010 to 2015, mean heart doses were 5.2 Gy and 3.7 Gy in left-sided and right-sided RT, respectively [11]. We recently showed considerably lower doses in a dosimetry study of 182 BC patients selected from the same registry as the present study, although including only patients undergoing coronary angiography due to a cardiac event [27]. The median mean heart dose was 0.6 Gy (interquartile range (IQR) 0.4-1.0) after right-sided RT and 2.7 Gy (IQR 1.7-4.2) after left-sided RT.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In a recent systematic review of trials from 2010 to 2015, mean heart doses were 5.2 Gy and 3.7 Gy in left-sided and right-sided RT, respectively [11]. We recently showed considerably lower doses in a dosimetry study of 182 BC patients selected from the same registry as the present study, although including only patients undergoing coronary angiography due to a cardiac event [27]. The median mean heart dose was 0.6 Gy (interquartile range (IQR) 0.4-1.0) after right-sided RT and 2.7 Gy (IQR 1.7-4.2) after left-sided RT.…”
Section: Discussionmentioning
confidence: 44%
“…The median mean heart dose was 0.6 Gy (interquartile range (IQR) 0.4-1.0) after right-sided RT and 2.7 Gy (IQR 1.7-4.2) after left-sided RT. Moreover, the left/right RT dose difference was higher in the mid and distal LAD, where median mean doses were 3.6 Gy (IQR 2.4-6.2) and 26.7 Gy (IQR 7.0-41.0) after left-sided RT, and 0.5 Gy (IQR 0.1-0.8) and 0.3 Gy (IQR 0.1-0.8) after right-sided RT, respectively [27].…”
Section: Discussionmentioning
confidence: 92%
“…While MHD certainly is a surrogate for overall cardiac dose, especially in an older era before more conformal treatments, it does not always adequately represent dose to individual cardiac substructures and their consequent late effects. Nilsson et al demonstrated how the location of radiation hot spots in the coronary arteries, and in more modern series, specific doses to the LAD, correlate with degree of stenosis and the requirement of coronary intervention of these specific areas . Other reports have established that various cardiac substructures such as left ventricle, cardiac valves, and left circumflex artery are predictors of cardiotoxicity .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous dosimetry study, patients with left breast cancer had absorbed a dose of 2.3 ± 0.7 Gy to the heart and the left anterior descending coronary artery showed the highest radiation dose (7.6 ± 4.5 Gy) among the coronary arteries, while all patients with right breast cancer had absorbed a dose lower than 2.0 Gy [5]. These results emphasize the need to develop advanced RT techniques that can reduce the radiation dose to the heart and to screen patients with left breast cancer for radiation-induced heart disease [4,9,10].…”
Section: Introductionmentioning
confidence: 84%
“…Adjuvant RT reduces the risk of mortality by 16% and that of local recurrence by more than 50% in patients with breast cancer [1,3]. However, for patients with left breast cancer, some territory of the heart is often included in the RT field, which could result in radiation-induced damage to the myocardium and coronary artery [4,5], and previous clinical studies have reported increased risk of ischemic heart disease, myocardial infarction, and cardiac disease-related mortality in patients with left breast cancer compared to those with right breast cancer [6][7][8]. In a previous dosimetry study, patients with left breast cancer had absorbed a dose of 2.3 ± 0.7 Gy to the heart and the left anterior descending coronary artery showed the highest radiation dose (7.6 ± 4.5 Gy) among the coronary arteries, while all patients with right breast cancer had absorbed a dose lower than 2.0 Gy [5].…”
Section: Introductionmentioning
confidence: 99%